2015
DOI: 10.1016/j.yhbeh.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in diurnal rhythms of food intake in mice caused by gonadal hormones and complement of sex chromosomes

Abstract: We measured diurnal rhythms of food intake, as well as body weight and composition, while varying three major classes of sex-biasing factors: activational and organizational effects of gonadal hormones, and sex chromosome complement (SCC). Four Core Genotypes (FCG) mice, comprising XX and XY gonadal males and XX and XY gonadal females, were either gonad-intact or gonadectomized (GDX) as adults (2.5 months); food intake was measured second-by-second for 7 days starting 5 weeks later, and body weight and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 32 publications
(43 reference statements)
7
46
0
Order By: Relevance
“…The unmasking of different metabolic profiles with sex is not a surprise. In recent years, several studies have used the sex chromosome complement model to unmask differences in rhythms of activity [22], food intake [22, 23], and lipoprotein levels [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The unmasking of different metabolic profiles with sex is not a surprise. In recent years, several studies have used the sex chromosome complement model to unmask differences in rhythms of activity [22], food intake [22, 23], and lipoprotein levels [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The weight difference between XX and XY mice was amplified by a high fat diet, becoming statistically significant after merely 3 days on the diet. The increased obesity in XX mice was associated with increased food intake during the light (inactive) phase of the circadian cycle (21, 22). Along with increased adiposity, XX mice developed fatty liver and had elevated levels of fasting insulin (Figure 5), both of which are co-morbidities of obesity in humans.…”
Section: Genetic Contributions To Sex Differences In Adiposity Anmentioning
confidence: 99%
“…The major effect of chromosome complement on energy balance was on food intake. Continual monitoring of FCG mouse food intake for several days [24] to weeks [25] revealed that 4 weeks after gonadectomy, female mice tend to eat more than male mice during the dark phase, but that during the light phase XX mice eat more than XY mice, regardless of the original gonad type. The difference between female and male food intake at 4 weeks post- gonadectomy may be attributable to lingering effects of gonadal hormones, as this effect was not apparent at 10 months after gonadectomy [24].…”
Section: XX Sex Chromosome Complement Is a Risk Factor For Obesitymentioning
confidence: 99%
“…The difference between female and male food intake at 4 weeks post- gonadectomy may be attributable to lingering effects of gonadal hormones, as this effect was not apparent at 10 months after gonadectomy [24]. Interestingly, the increased food intake in XX compared to XY mice was associated with a shift in feeding rhythm, with early onset of feeding at the end of the light phase in anticipation of normal feeding time at the beginning of the dark phase [25]. There is evidence that altered circadian cycle or increased feeding during the light phase of the circadian cycle leads to increased weight gain in mice [2628].…”
Section: XX Sex Chromosome Complement Is a Risk Factor For Obesitymentioning
confidence: 99%